KAJIAN SIFAT KUALITATIF DAN KUANTITATIF HASIL PERSILANGAN BLEWAH LOKAL LOMBOK DAN MELON - lestari ujianto; Uyek Malik Yakop; Suprayanti Martia Dewi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
The offspring resulting from crosses between local Lombok cantaloupe and melon plants have a lot of genetic diversity in both qualitative and quantitative traits. The aim of this study was to determine the qualitative and quantitative characteristics of offspring resulting from crosses between local Lombok cantaloupe and melon. The study consisted of two activities, namely crosses between local Lombok cantaloupe and melon plants. The crosses consisted of two local Lombok cantaloupe genotypes (BH and BL) and two melon genotypes (MK and MP) resulting in eight offspring. The study used a completely randomized block design to evaluate 12 genotypes consisting of four parental genotypes and eight offspring genotypes. The observed traits included plant length, harvest age, fruit length, fruit diameter, fruit flesh thickness, fruit sweetness, and fruit weight. The results showed that the success rate of crosses between cantaloupe and melon ranged from 62.1% to 77.4%. The viability rate in the cross-bred offspring population was high, ranging from 90% to 98%. Both qualitative and quantitative traits of the offspring resulting from crosses were generally between the characteristics of the two parents. Several offspring had different characteristics compared to their parents. The observed quantitative traits had varying GCD and heritability values. GCD values ranged from 8.3% to 27.4%, and heritability values ranged from 25.51% to 58.41%.